(untitled) (Journal of Contemporary Issues in Accounting, 2026)
This study evaluated the effect of credit risk on the performance of deposit money banks listed on the floor of Nigerian Exchange Group. Net asset per share was used as a proxy for the the dependent variable, performance while market quality ratio and assets quality ratio served as proxies to the independent variable, credit risk management. A sample of 12 deposit money banks were used for the period of eleven years spanning 2012 to 2022. The study employed ex-post facto and longitudinal research design. Data were collected from annual reports of the selected deposit money banks and five (5) specific objectives and hypotheses were subjected to some preliminary data tests like descriptive statistics. Pearson correlation analysis and Variance Inflation factor (VIF) were analyzed using panel regression analysis. Using a sample of 132 banks-year observations, the result revealed that management quality ratio has statistical significant effect on market performance of deposit money banks in Nigeria. It was also discovered that asset quality ratio has negative and insignificant effect on market performance of deposit money banks in Nigeria which was statistically insignificant at 5% level of significance. It was therefore concludedthat banks engaging in risk projects can either lose or gain and that informed decisions need to be adhered to in such scenarios. Based on these findings, the study recommended that banks should fully concentrate on the loan assessment procedure, polices and quality of loans and liquidity management. Nigeria banking industry should inculcate a balance credit risk management culture to mitigate risks and shocks..